Postinfectious Bronchiolitis Obliterans in Children: Diagnostic Workup and Therapeutic Options: A Workshop Report. (31st January 2020) - Jerkic, Silvija-Pera; Brinkmann, Folke; Calder, Alistair; Casey, Alicia; Dishop, Megan; Griese, Matthias; Kurland, Geoffrey; Niemitz, Mandy; Nyilas, Sylvia; Schramm, Dirk; Schubert, Ralf; Tamm, Michael; et al.
Abstract : Bronchiolitis obliterans (BO) is a rare, chronic form of obstructive lung disease, often initiated with injury of the bronchiolar epithelium followed by an inflammatory response and progressive fibrosis of small airways resulting in nonuniform luminal obliteration or narrowing. The term BO comprises a group of diseases with different underlying etiologies, courses, and characteristics. Among the better recognized inciting stimuli leading to BO are airway pathogens such as adenovirus and mycoplasma, which, in a small percentage of infected children, will result in progressive fixed airflow obstruction, an entity referred to as postinfectious bronchiolitis obliterans (PIBO). The present knowledge on BO in general is reasonably well developed, in part because of the relatively high incidence in patients who have undergone lung transplantation or bone marrow transplant recipients who have had graft-versus-host disease in the posttransplant period. The cellular and molecular pathways involved in PIBO, while assumed to be similar, have not been adequately elucidated. Since 2016, an international consortium of experts with an interest in PIBO assembles on a regular basis in Geisenheim, Germany, to discuss key areas in PIBO which include diagnostic workup, treatment strategies, and research fields.